Pengaruh Penggunaan Instagram terhadap Perubahan Perilaku Keagamaan dan Sosial pada Generasi Z - Ar'robby, Muzdalifah; Faradila, Faja; Damayanti, Mahmudah Widya; Ridho, Kholis (Universitas Islam Balitar, 2025)
The objective of this research is to examine the influence of Instagram use on religious and social behavior changes among Generation Z. A quantitative approach with a descriptive correlational design was applied using a questionnaire as the main instrument. Data analysis included Pearson correlation and multiple linear regression. Results indicated that Instagram usage duration significantly affects changes in religious behavior (r=0.334; p<0.01) and social behavior (r=0.521; p<0.01), while frequency and intensity showed weaker effects. Longer usage duration increases the risk of neglecting religious activities and decreases face-to-face interaction intensity. This study highlights the importance of managing social media usage time to maintain the balance of religious and social life among Generation Z.